Modern scientific and practical approaches to healthcare of student youth - О.І. Погребняк; О.А. Согоконь (H.S. Skovoroda Kharkiv National Pedagogical University, 2017)
Before the system of higher education, there was an urgent need for a transition to an innovative type of education, which should be based on the concern for the health of the younger generation. The state has a duty to continuously improve, in accordance with international standards, health-improving technologies in the field of physical education. The main task of the higher school is to preserve and develop the intellectual and physical potential of the nation, which is achieved through physical activity. Modern education is characterized by a wide introduction of technological approach. In this article the special attention is spared to the problem of providing of  forming and maintenance of  heath, the decision of that lies in the special construction education-educator process. It is well-proven by us, that athletic-heath work is correctly organized in higher educational establishment can become basics of rational organization of the motive mode of students, will assist to physical development and motive prepared nests will allow to promote potential possibilities of organism of future doctors.